PENGARUH KEPEMIMPINAN, IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI YAYASAN AL-HUDA - Husna, Ramelia Nikmatul (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
This research aims to express: (1) Effect of Leadership, Organizational Climate and Work Motivation Against simultaneously, (2) Effect of Leadership, Organizational Climate and Work Motivation partially Against Teacher Performance Yayasan Al-Huda in Pekanbaru. The study population was all the Masters in Yayasan Al-Huda Pekanbaru, amounting to 76 people. Samples were taken from all the population that is 76 people. The results showed: 1) simultaneously Leadership, OrganizationalÂ Climate and Work Motivation positive and significant impact on the performance of teachers. Effect of Leadership (X1) organizational climate (X2), work motivation (X3) simultaneously on the performance of teachers (Y) is 12.957 with a significance value of 0000. If the significance value compared with the significance level used in this study (a = 0.05), it is evident that the significance value is smaller than (0.000 <0.05), it can be said that the leadership (X1) organizational climate (X2), work motivation (X3) proved positive and significant impact on teacher performance in Yayasan Al-Huda Pekanbaru. 2) Partially There is a positive and significant impact on the performance leadership variables Teacher At Al-Huda Foundation Pekanbaru. Which gained significantly smaller levels of alpha (0.016 <0.05). That is the good leadership increased the Teacher Performance In Al-Huda Foundation Pekanbaru., Partially There is no significant positive influence and organizational climate variables on the performanceÂ of teachers In Al-Huda Foundation Pekanbaru. Which gained significantly greater levels of alpha (0.337> 0.05), Partially There is a positive and significant impact on the performance of work motivation of teachers In Al-Huda Foundation Pekanbaru, Which gained significantly smaller levels of alpha (0.000 <0.05)Namely multiple linear regression equation Y= 12.502 + 0.283 X1 + 0.085 X2 + X3 0454